2016
DOI: 10.1371/journal.pone.0166849
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Administration of ADSCs-Based Therapy and Gene Therapy Using Ad-huPA Reduces Experimental Liver Fibrosis

Abstract: Background and AimshADSCs transplantation in cirrhosis models improves liver function and reduces fibrosis. In addition, Ad-huPA gene therapy diminished fibrosis and increased hepatocyte regeneration. In this study, we evaluate the combination of these therapies in an advanced liver fibrosis experimental model.MethodshADSCs were expanded and characterized before transplantation. Ad-huPA was simultaneously administrated via the ileac vein. Animals were immunosuppressed by CsA 24 h before treatment and until sac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 27 publications
1
11
0
2
Order By: Relevance
“…Rivera-Valdes et al demonstrated that ADSCs could reverse chronic kidney fibrosis through the suppression of CTGF gene expression, in addition to IL6, IL10- TNF and TGF-β1 [55]. Similarly, liver fibrosis was reversed by ADSCs intravenous injection through the down regulation of pro-collagen alpha1, CTGF and α-SMA mRNA [56].…”
Section: Discussionmentioning
confidence: 99%
“…Rivera-Valdes et al demonstrated that ADSCs could reverse chronic kidney fibrosis through the suppression of CTGF gene expression, in addition to IL6, IL10- TNF and TGF-β1 [55]. Similarly, liver fibrosis was reversed by ADSCs intravenous injection through the down regulation of pro-collagen alpha1, CTGF and α-SMA mRNA [56].…”
Section: Discussionmentioning
confidence: 99%
“…The function of HPC activation in liver fibrogenesis vs regeneration is controversial (Michalopoulos and Bhushan, 2021;Williams et al, 2014). Partial hepatectomy in fibrotic liver was previously reported to drive pro-fibrogenic HPC activation that impaired liver regeneration (Kuramitsu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 overexpression promoted a pro-resolving macrophage phenotype and improved liver regeneration in cirrhotic mice (Melgar-Lesmes et al, 2018). Urokinase plasminogen activator (Plau) therapy ameliorated fibrosis in the CCL4 model via activation of latent metalloproteinases and HGF (Bueno et al, 2006;Meza-Rios et al, 2016;Salgado et al, 2000). Fibrosis regression occurred despite high expression of the canonical profibrogenic cytokine Tgfb1 and, in some cases, the proinflammatory cytokines Il6 and Tnf, which have frequently been shown to diminish in the resolution phase of disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene therapy consists in the delivery of therapeutic genes to a target organ through different type of vectors, where viral vectors are mostly used. Our research group has demonstrated the therapeutic effect of different human proteins like urokinase Plasminogen Activator (uPA) [ 11 , 12 ], ΔTGFbRII [ 13 ] (TGFβ1 truncated receptor) and MMP8 [ 10 , 14 , 15 ] coded by cognate cDNAs resulting in significantly reduced fibrotic tissue in experimental cirrhosis models. Thus, the aim of this study was to expand our knowledge in other fibrotic organs, and evaluate the therapeutic effect on kidney fibrotic tissue via administration of a recombinant human MMP8 cDNA cloned in an adenoviral vector in an adenine-induced CKD experimental model.…”
Section: Introductionmentioning
confidence: 99%